2008
DOI: 10.1038/nsmb.1496
|View full text |Cite
|
Sign up to set email alerts
|

Insights into interferon regulatory factor activation from the crystal structure of dimeric IRF5

Abstract: Interferon regulatory factors (IRFs) are essential in the innate immune response and other physiological processes. Activation of these proteins in the cytoplasm is triggered by phosphorylation of Ser/Thr residues in a C-terminal autoinhibitory region, which stimulates dimerization, transport into the nucleus, assembly with the coactivator CBP/p300 and initiation of transcription. The novel crystal structure of the transactivation domain of pseudophosphorylated human IRF5 reveals a striking dimer in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
146
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 51 publications
5
146
0
Order By: Relevance
“…6B), whose phosphorylation by TBK1 is important for the nuclear translocation of IRF3. Ser462 of IRF5 is positioned within hydrogen-bonding distance of Arg354, an arginine residue that is conserved in IRF3 (24). The phosphorylation of Ser462 of IRF5 or Ser396 of IRF3 may therefore induce an interaction between the phosphoserine and arginine residues that stabilizes the dimeric form of IRF5 and permits its nuclear translocation and the stimulation of gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…6B), whose phosphorylation by TBK1 is important for the nuclear translocation of IRF3. Ser462 of IRF5 is positioned within hydrogen-bonding distance of Arg354, an arginine residue that is conserved in IRF3 (24). The phosphorylation of Ser462 of IRF5 or Ser396 of IRF3 may therefore induce an interaction between the phosphoserine and arginine residues that stabilizes the dimeric form of IRF5 and permits its nuclear translocation and the stimulation of gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies demonstrating that IRF4-deficient CD4 + T cells cannot upregulate RORγt upon exposure to Th17 skewing conditions (11), IRF4 phosphorylation was also important for the ability of IRF4 to directly target the RORγt promoter and for the induction of RORγt. Interestingly, the 2 serines targeted by ROCK2, S446 and S447, are contained within an α-helical region of IRF4 located carboxyterminal of the IRF association domain (55). Structural studies of IRF3 and IRF5 have demonstrated that this region serves an autoinhibitory function and that its phosphorylation triggers a conformational rearrangement that relieves the autoinhibition (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the 2 serines targeted by ROCK2, S446 and S447, are contained within an α-helical region of IRF4 located carboxyterminal of the IRF association domain (55). Structural studies of IRF3 and IRF5 have demonstrated that this region serves an autoinhibitory function and that its phosphorylation triggers a conformational rearrangement that relieves the autoinhibition (55)(56)(57). Despite sharing structural similarities, the carboxyterminal regions of different IRFs exhibit very low sequence similarity (55).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the STING (or RLR) pathway enhances the association of IRF3 and TBK1, a process essential to IRF3 activation by TBK1. However, phosphorylated IRF3 must promptly dissociate from TBK1 to undergo the conformational changes required for its dimerization (5,25). Hence, if IRF3 remains associated with TBK1 by additionally interacting molecules induced/activated by TLR4-MyD88 signaling, the IRF3 activation processes would be inhibited.…”
Section: Enhancement Of Irf3-tbk1 Association By Tlr-myd88 Signalingmentioning
confidence: 99%